2021
DOI: 10.2147/jbm.s309425
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia Among Children Who Attended the Children’s Teaching Hospital in Karbala, Iraq

Abstract: Introduction The World Health Organization (WHO) reported a moderate incidence of anaemia among pregnant and nonpregnant women and among children younger than 59 months in 2011. Purpose The aim of this study was to investigate anaemia among children younger than 14 years submitted to haematological exams at the Children’s Teaching Hospital in Karbala, Iraq. Patients and Methods This was a cross-sectional study carried out in the Children’s Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In a comprehensive study by Albaroodi et al, the prevalence of IDA in Iraq was found to be increasing due to factors such as inadequate dietary intake, poor iron absorption, and parasitic infections (Albaroodi, 2021). The authors emphasized the importance of addressing the growing burden of IDA on the healthcare system and the overall well-being of affected populations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In a comprehensive study by Albaroodi et al, the prevalence of IDA in Iraq was found to be increasing due to factors such as inadequate dietary intake, poor iron absorption, and parasitic infections (Albaroodi, 2021). The authors emphasized the importance of addressing the growing burden of IDA on the healthcare system and the overall well-being of affected populations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Iron deficiency anemia (IDA) is a pervasive public health issue that disproportionately affects populations in developing countries (World Health Organization, 2021). Iraq country, is no exception to this global challenge, as it faces unique social, economic, and infrastructural barriers that contribute to the high prevalence of IDA (Albaroodi, 2021). This study aims to explore the prevalence of iron deficiency anemia among various age groups in Duhok, Iraq, and identify potential risk factors and interventions that could mitigate this pressing health concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation